Language choice among family in Narum speech community - Sa’adiah Ma’alip; Kartini Abd Wahab (Penerbit Universiti Kebangsaan Malaysia, 2024)
Whenever speakers of two or more languages communicate, a decision has to be made about which of these languages is to be used. This study focuses on the language choice among family in Narum Community. This study is significant in that i) very little research of any kind has been done on the Narum community, ii) the community is in a late stage of language shift; iii) the contribution of the present study will be the documentation of the Narum language and community. The present study investigates the community’s language choice among their family members. A set of questionnaires with 180 respondents was used to obtain the data. The respondents being randomly selected in the interests of assessing the importance and significance of Narum language choice. The data and follow-up analysis make use of Fishman’s domain analysis. The study employs descriptive frequencies using SPSS. Often no satisfactory explanation can be given as to why speakers make the choices they do, but studies show that a speech community and its language choice is determined by the members of the community itself. It suggests a linear trend towards the Sarawak Malay language in line with the speakers' exposure thereto. Notable is the discrepancy in language choice of the Narum community, with a more pronounced gravitation towards the Sarawak Malay language during interaction with family members. The results of the language choice with a peer group show that both younger and older generations choose to use the Sarawak Malay language. The study concludes that the efforts to maintain this language in the future will depend on the Narums desire to retain to their native language.